Effectiveness of Flood Management Policies in Sungai Pinang District, Samarinda City - Andi Fajar Asti; Diana Mayasari (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study is to identify flood problems occurring in Sungai Pinang District, Samarinda City and analyze the effectiveness of implementing government policies to address flooding problems in Sungai Pinang, Samarinda City. The research method in this article uses a descriptive research design. Based on the type of research and data sources used, data collection techniques in this study used secondary data. Then the results of the research that has been done is that the causes of flooding in Sungai Pinang Subdistrict are the dynamics and development of the city growing rapidly, population growth is increasing then there is a shift in land